2007
DOI: 10.1159/000103182
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the turkey MHC chromosome through genetic and physical mapping

Abstract: Previous studies in the chicken have identified a single microchromosome (GGA16) containing the ribosomal DNA (rDNA) and two genetically unlinked MHC regions, MHC-B and MHC-Y. Chicken DNA sequence from these loci was used to develop PCR primers for amplification of homologous fragments from the turkey (Meleagris gallopavo). PCR products were sequenced and overgo probes were designed to screen the CHORI 260 turkey BAC library. BAC clones corresponding to the turkey rDNA, MHC-B and MHC-Y were identified. BAC end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
(36 reference statements)
2
27
0
Order By: Relevance
“…For example, MHC class I and class II molecules are necessary for antigen presentation to T lymphocytes and are common to the galliform MHC [229][230][231][232][233][234][235][236][237]. In turkeys and chickens, the MHC is composed of 2 genetically unlinked regions, the B-locus (MHC-B) and Y-locus (MHC-Y), co-located on a single microchromosome (GGA16 or MGA18, respectively) [229][230][231][232][233][234][235][236][237]. Although some genes are well characterized, the functions and expression patterns of many poultry MHC genes are still unknown.…”
Section: Cytokines and The Mhcmentioning
confidence: 99%
“…For example, MHC class I and class II molecules are necessary for antigen presentation to T lymphocytes and are common to the galliform MHC [229][230][231][232][233][234][235][236][237]. In turkeys and chickens, the MHC is composed of 2 genetically unlinked regions, the B-locus (MHC-B) and Y-locus (MHC-Y), co-located on a single microchromosome (GGA16 or MGA18, respectively) [229][230][231][232][233][234][235][236][237]. Although some genes are well characterized, the functions and expression patterns of many poultry MHC genes are still unknown.…”
Section: Cytokines and The Mhcmentioning
confidence: 99%
“…A clone from the library (97E05) containing a portion of the MHC-B region was isolated previously (27). Screening for additional BAC clones was performed as previously described (33) using overlapping oligonucleotide probes based on the end sequences of clone 97E05 (GenBank accession nos.…”
Section: Sequencing Strategymentioning
confidence: 99%
“…Recent work (27) in the turkey has identified two MHC regions homologous to the chicken B and Y loci. Bacterial artificial chromosome (BAC) 4 clones containing portions of these regions were physically mapped to turkey metaphase chromosomes through fluorescent in situ hybridization and genetically mapped by segregation analysis using a resource population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SSCP analysis showed that chicken TAP genes are highly polymorphic (Walker et al, 2005). For turkey, by characterization of the chromosome bearing the MHC locus, sequence homology between chicken and turkey was identified, and the presence of TAP1 gene was reported, but not TAP2 (Chaves et al, 2007). Recently, the same authors have updated the MHC partial sequence and added the TAP2 gene sequence data (Accession #DQ993255).…”
Section: Introductionmentioning
confidence: 99%